A strange familiarity? Place perceptions among the globally mobile. (August 2014) - Pristed Nielsen, Helene; Thidemann Faber, Stine
How do globally mobile people perceive and make sense of a new place in which they have to create an everyday life for themselves? And how may their place perception be communicated through photographs? These are the questions around which this article revolves. The visual material discussed in the article stems from a participatory research project, in which North Denmark functions as a setting for studying local particularities and global convergences. Analysing part of this material, the article explores the perception of – and affiliation with – places and localities, pointing to how perceptions of strangeness and familiarity occur along unexpected lines of difference and similarity depending on the embodied positionality of the involved participants.